The Influence of advertising appeal, service features, and price on customer satisfaction of Tiket.com application users in Medan - Nichola Verymo Sitepu; Maisara Batubara; Jeffrey Maurits; Enci Simalango; Kristiodora Sijabat; Ezzah Nahrisah (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2026)
This study was conducted on Tiket.com application users in Medan City. This study was conducted with the aim of testing and analyzing the influence of advertising appeal, service features, and price on customer satisfaction in Medan City. This study used a quantitative research method. The data processing technique used SEM-PLS, which consists of two tests, namely the outer model and inner model. The population in this study was all Tiket.com users in Medan, whose exact number is unknown, so the sample consisted of 150 respondents. Advertising appeal had a t-statistic value (0.503> 1.987) with a P value of (0.615 < 0.05), indicating that there is no significant effect on the customer satisfaction of Tiket.com app users. Service Features had a statistical t-value (3.195 > 1.987) with a P-value (0.001 > 0.05), so it can be stated that there is a positive and significant effect on Customer Satisfaction among users of the Tiket.com application. Price has a t-statistic value (7.075 > 1.987) with a P-value (0.000< 0.05), so it can be stated that there is a significant effect on the customer satisfaction of Tiket.com app users. Advertising Appeal, Service Features, and Price simultaneously have a P-value of 0.000 < 0.05, so it can be concluded that Advertising Appeal, Service Features, and Price simultaneously affect the Customer Satisfaction of Tiket.com app users